Changing Transatlantic Security Relations : Do the U. S, the EU and Russia Form a New Strategic Triangle? - Hallenberg, Jan. (Contemporary Security Studies, 2006)
The strategic triangle is used as an organizing principle for the study of the security relationships among the United States, the EU and Russia in the greater transatlantic sphere.